Kota Qom Sebagai Pusat Pendidikan Madzhab Syi’ah: Sejarah dan Perkembangannya - El-Razy, KM. Ridho; Asari, Hasan; Badaruddin, KMS.; Zailia, ST; Fahira, Dina (El-Idare, 2023)
Sensitive issues of the mazhaban between Sunni and Shi'a are increasingly rife in filling the information space of Indonesian society, especially after the outbreak of the Syrian Civil War. In addition, Indonesian students who graduated from the city of Qom, Iran, are considered to be the newest generation of Shiites who have a mission to spread syi'ahism and are often in conflict with other groups. This paper attempts to answer the formulation of the problem, "how is the history and development of the City of Qom as a center for Shi'a school of education in Iran?" The writing methodology used is based on a qualitative approach through historical investigations by conducting documentation data collection studies. This research proves that Qom has become an important Shiite base in Persia since many Alawites (descendants of Ali bin Abi Talib) migrated in the early centuries of Islamic times. Then, between the 9th and 10th centuries, two important sites for Shi'ite pilgrimage stood, namely the Tomb of Fatima Ma'shumah and the Jamkaran Mosque. In the same range, the Fuqaha of the Early Shi'a generation lived here, namely Shaykh Shaduq and Shaykh Al-Kulaini. However, Qom's vital role strengthened in the Safavid to Qajar periods between the 16th and 19th centuries with the Feiziyeh Madrasa as its icon. Shi'ite philosophers also worked there, including Mulla Shadra and Mulla Al-Razzaq Lahiji. Although weakened in the early 20th century, Ayatollah Haeri Yazdi's role in establishing the Qom Scholars' Seminary/Seminary in 1922 marked an advance that even rivaled Najaf as a center for Shi'i education. Ayatollah Khomeini was a major figure who graduated from that school which made Qom the base of the 1979 Iranian Revolution. Until now, this city has been taken into account in Islamic education.